1999
DOI: 10.1021/ic990556r
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and Dynamics of Re4+ Near-IR-to-Visible Luminescence Upconversion

Abstract: Intense visible upconversion luminescence is observed in a Re(4+)-doped low-phonon host material, Cs(2)ZrCl(6), with excitation in the near-infrared. The upconversion excitation wavelength, temperature, power, and time dependence is studied using variable-temperature absorption and luminescence spectroscopies, and modeled using a three-level set of coupled nonlinear rate equations. On the basis of analysis of these data, energy-transfer upconversion is shown to be the dominant mechanism responsible for this ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
80
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 36 publications
6
80
0
1
Order By: Relevance
“…The cross‐relaxation of 1 T 2 → 3 T 2 + 3 A 2 → 3 T 1 quenches the 1 T 2 → 3 A 2 green UC emission of Ni 2+ in MgF 2 when pumped by 752.5 nm laser,21 see Figure 4c. Re 4+ was the first TM ion studied in UC material22 and the first TM ion to show RT UC phenomenon owing to the relaxation of the spin selection rules by its strong spin‐orbit coupling 23. The UC‐emitting state Γ 7 ( 2 T 2g ) has a branching ratio of 1:2 for luminescence to ground state Γ 8 ( 4 A 2g ) relative to the intermediate excited state Γ 8 ( 2 E g ).…”
Section: Photon Upconversion Of Tm Ionsmentioning
confidence: 99%
“…The cross‐relaxation of 1 T 2 → 3 T 2 + 3 A 2 → 3 T 1 quenches the 1 T 2 → 3 A 2 green UC emission of Ni 2+ in MgF 2 when pumped by 752.5 nm laser,21 see Figure 4c. Re 4+ was the first TM ion studied in UC material22 and the first TM ion to show RT UC phenomenon owing to the relaxation of the spin selection rules by its strong spin‐orbit coupling 23. The UC‐emitting state Γ 7 ( 2 T 2g ) has a branching ratio of 1:2 for luminescence to ground state Γ 8 ( 4 A 2g ) relative to the intermediate excited state Γ 8 ( 2 E g ).…”
Section: Photon Upconversion Of Tm Ionsmentioning
confidence: 99%
“…1. We have previously shown that Re 4+ in an octahedral F − , Cl − , and Br − environment is capable of NIR to VIS photon upconversion [5][6][7]. This is due to the fact that the Re 4+ excitations shown in Fig.…”
Section: Introductionmentioning
confidence: 96%
“…1, being simple spin flips, couple very weakly to the lattice, and bear a lot of similarity to the f-f excitations in lanthanides. In Re 4+ doped Cs 2 ZrCl 6 [6] and Cs 2 ZrBr 6 [7] excitation into the Re 4+ [ 2 E g / 2 T 1g ] multiplet between 8000 and 10 000 cm −1 leads to red Re 4+ [ 7 ( 2 T 2g )] emission at all temperatures between 10 and 300 K. This is a rather inconvenient excitation region, both in the laboratory and for possible applications.…”
Section: Introductionmentioning
confidence: 99%
“…UCProzesse konnten in einer großen Anzahl von mit Über-gangsmetallionen dotierten Wirtgittern, z. B. für Ti 2+ -, [17,18] Ni 2+ -, [19][20][21][22] Mo 3+ -, [23,24] Re 4+ - [23,25,26] oder Os 4+ -dotierte Festkörper, [27][28][29][30] nachgewiesen werden. Auch Actinoid-dotierte Materialien wurden auf ihre UC-Eigenschaften untersucht.…”
Section: Introductionunclassified